Artificial intelligence regulation in the United Kingdom: A path to good governance and global leadership? - Huw Roberts; Alexander Babuta; Jessica Morley; Christopher Thomas; Mariarosaria Taddeo; Luciano Floridi (Internet Policy Review, 2023)
On 29 March 2023 the United Kingdom (UK) government published its AI Regulation White Paper, a "proportionate and pro-innovation regulatory framework" for AI designed to support innovation, identify and address risks, and establish the UK as an "AI superpower". In this article, we assess whether the approach outlined in this policy document is appropriate for meeting the country's stated ambitions. We argue that the proposed continuation of a sector-led approach, which relies on existing regulators addressing risks that fall within their remits, could support contextually appropriate and novel AI governance initiatives. However, a growing emphasis from the central government on promoting innovation through weakening checks, combined with domestic tensions between Westminster and the UK's devolved nations, will undermine the effectiveness and ethical permissibility of UK AI governance initiatives. At the same time, the likelihood of the UK's initiatives proving successful is contingent on relationships with, and decisions from, other jurisdictions, particularly the European Union. If left unaddressed in subsequent policy, these factors risk transforming the UK into a reluctant follower, rather than a global leader, in AI governance. We conclude this paper by outlining a set of recommendations for UK policymakers to mitigate the domestic and international risks associated with the country's current trajectory.
Keywords: 300; AI governance; United Kingdom; Brussels Effect; Ethics; Artificial intelligence